Location and severity of root resorption related to impacted maxillary canines: a cone beam computed tomography (CBCT) evaluation - Doğramacı Esma J.; Sherriff Martyn; Rossi-Fedele Giampiero; McDonald Fraser (Australasian Orthodontic Journal, 2015)
The present investigation was designed to determine the location and severity of root resorption associated with impacted maxillary canine teeth using cone beam computed tomography (CBCT). A secondary aim was to identify possible influencing factors.